Search for SARS-CoV-2 Inhibitors. Is it still needed?Molecular Docking Study of Teicoplanin Derivatives and Vancomycin against SARS-CoV-2 Mpro - Mulyani, Sri; Lestari, Nova Dwi; Samodra, Imam; Wibowo, Fajar Rakhman; VH, Elfi Susanti; Ardyanto, Tonang Dwi (Jurnal Kimia Valensi, 2025)
Coronaviruses have been known since 2002 in the case of SARS (Severe Acute Respiratory Syndrome). SARS-CoV-2, the cause of the COVID-19 pandemic, is believed to be an evolution of the SARS-causing coronavirus (SARS-CoV). This evolution shows the complex interaction dynamics between the virus and the host, which have characterized the emergence of new SARS-CoV-2 strain variations until now. Therefore, the search for these antiviral drugs is still critical. MPro is one of the important proteins for the life cycle of pathogenic coronaviruses, so it is an attractive target for developing drugs that inhibit this virus. This study examined the interaction of teicoplanin derivatives and vancomycin as SARS-CoV-2 MPro (6LU7) inhibitors through molecular docking with Autodock Vina. The smallest RMSD value was selected and stored to calculate the energy value. The image of atoms in the ligand and receptor was processed with Autodock Tools, LigPlus, and PyMOL. The study showed that teicoplanin derivatives such as teicoplanin aglycone, teicoplanin-A3-1, and vancomycin had the potential as SARS-CoV-2 Mpro inhibitors. Based on the interaction at the active site and the obtained ΔG values, even the teicoplanin aglycon had a more significant inhibitory potential than other potent inhibitors such as N3.